Antiinflamasi - Haryanto Haryanto; Aqilah Najwa Nabila; Siti Nurhalisa; Adinda Aulia Ramadhani; Syamsinar Syamsinar; Abid Mansyur Borut; Erfina Amalia; Nurul Ayu Tri Ulfia (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Pharmacology is the study of drug interactions with living organisms. This study aims to evaluate the anti-inflammatory effects of several drug preparations, including Hemilon (methylprednisolone), Lupred (prednisolone), Kamathasone (dexamethasone), neem leaf infusion, and snakehead fish extract, on mice (Mus musculus) induced with inflammation using carrageenan solution via intraplantar injection. Edema volume was observed using a plethysmometer at 15, 30, 45, and 60 minutes post-induction. Data were analyzed using normality, homogeneity, ANOVA, and Tukey tests via SPSS. Results showed that Hemilon had the highest anti-inflammatory effect, followed by Kamathasone and Lupred, while neem leaf and fish extract showed weaker activity. Statistical tests revealed normal distribution (sig. 0.197 > 0.05), non-homogeneous data (sig. 0.022 < 0.05), and no significant difference between groups (ANOVA sig. 0.366 > 0.05). Despite this, descriptive results confirmed strong anti-inflammatory potential of synthetic drugs. This practicum provides valuable insights into drug mechanisms and emphasizes methodological accuracy in pharmacological testing.